Aspects of dental care for patients hospitalized in a medical clinic from a university hospital - Macedo, Maurício Pereira; Souza, Luana Carneiro Diniz; Corrêa, Rita da Graça Carvalhal Frazão; Lopes, Fernanda Ferreira (ABCS Health Sciences, 2020)
Introduction: The current context of multiprofessional approach in health is based on quality of care and patient safety, with the key contribution of the dentist in the hospital team to improve the health of hospitalized patients. Objective: To characterize the systemic and buccal profile of patients treated in a medical clinic of a University Hospital from the Brazilian Public Health System, aiming to provide information for guiding dental care in the multidisciplinary attendance in the hospital setting. Methods: Retrospective observational study carried out on 104 clinical records with data collection about general characteristics, systemic alterations, habits, oral situation and dental treatments of hospitalized patients attended by the dentist. Results: There was a high frequency of hypertensive patients (36.5%) and with cardiac problems (33.6%). A significant association between diabetes (60%) and hypertension (50%) in the age group from 60 to 75 years of age was observed. For most patients, the frequency of oral hygiene was less than three times a day (54.3%), without flossing (85.7%). Biofilm (73.3%), dental calculus (70.5%), prosthesis use (25.7%), with poor hygiene (14.3%) and prosthetic stomatitis (8.6%) were recorded. Among the treatments performed by dentist, basic periodontal therapy (71.4%) and exodontia (39%) were noteworthy. Conclusion: The high frequency of biofilm presence, dental calculus, prosthesis with poor hygiene and basic periodontal therapy performed during the hospitalization denote the need for dental care with preventive activities.